Ethanol sensing properties of Zn2TiO4 particles - Theerapong Santhaveesuk (2018)
© 2015 Elsevier Ltd and Techna Group S.r.l. All rights reserved. Zn < inf > 2 < /inf > TiO < inf > 4 < /inf > particles were prepared using the ball-milling technique in ethanol solution. Zn powder mixing with anatase-TiO < inf > 2 < /inf > powder at ratio of 2:1 by mole were used as raw materials. The mixed powders were grounded in agate mortar for 2 h, subsequently transferred into the ball-milled container with 1 mm zirconia balls and, then, milled for 24 h with ball-milling speeds of 200, 300 and 400 rpm. The ratio of powders and zirconia balls was 1:20 by weight. After that, the powders were washed using distilled water for 4 times, dried at 80 °C for 24 h and calcined at 1000 °C for 6 h. Morphological characteristics, chemical compositions, phase formation and defect of the synthesized powder were examined. The SEM result showed that the particle size was reduced as increase in the ball-milling speed, while the EDS showed that the Zn/Ti ratio was about 2. The XRD indicated that the synthesized powders exhibited a face center cubic Zn < inf > 2 < /inf > TiO < inf > 4 < /inf > phase, confirming by the Raman spectra. The Zn < inf > 2 < /inf > TiO < inf > 4 < /inf > particles were fabricated as the thick film ethanol sensor and tested under 50 and 200 ppm ethanol concentration at 300-500 °C. Our results suggest that the Zn < inf > 2 < /inf > TiO < inf > 4 < /inf > particles can be used for detection of ethanol vapor, and the sensor current increased with increasing of ethanol concentration. The highest sensitivity observed at 500 °C was 3.83 for 200 rpm, 1.92 for 300 rpm and 2.36 for 400 rpm samples. This implied that, the Zn < inf > 2 < /inf > TiO < inf > 4 < /inf > sensor can be a good candidate for high temperature application.